A triplex quantitative real-time PCR assay for differential detection of human adenovirus serotypes 2, 3 and 7 - Fang-zhou Qiu; Xin-xin Shen; Meng-chuan Zhao; Li Zhao; Su-xia Duan; Chen Chen; Ju-Ju Qi; Gui-xia Li; Le Wang; Zhi-shan Feng; Xue-jun Ma (Virology Journal, 2018)
Abstract Background Human adenovirus (HAdV) serotypes 2, 3 and 7 are more prevalent than other serotypes and have been associated with severe pneumonia in pediatric children. Molecular typing of HAdV is not routinely performed in clinical diagnostic laboratories as it is time-consuming and labor-intensive. Methods In the present study, we developed a triplex quantitative real-time PCR assay (tq-PCR) in a single closed tube for differential detection and quantitative analysis of HAdV serotypes 2, 3 and 7. The sensitivity, specificity, reproducibility and clinical performance of tq-PCR were evaluated. Results The analytical sensitivity of the tq-PCR was 100 copies/reaction for each of HAdV serotypes 2, 3 and 7, and no cross-reaction with other common respiratory viruses or HAdV serotypes 1,4,5,6,31,55 and 57 was observed. The coefficients of variation (CV) of intra-assay and inter-assay were between 0.6% to 3.6%. Of 138 previously-defined HAdV-positive nasopharyngeal aspirates samples tested, the detection agreement between tq-PCR and nested PCR was 96.38% (133/138). Conclusion The proposed tq-PCR assay is a sensitive, specific and reproducible method and has the potential for clinical use in the rapid and differential detection and quantitation of HAdV serotypes 2, 3 and 7.